Architecture of Learning Ecosystem Based on Islamic Education Management - Setyo Pamungkas; Nurfuadi Nurfuadi (CV. Edujavare Publishing, 2026)
Contemporary educational studies show that the quality of interactions, emotional climate, and learning space design significantly influence student academic achievement. This article aims to contextually reconstruct the architecture of the learning ecosystem in creating a conducive classroom environment based on Islamic educational management. This study uses a literature study approach by analyzing the theory of learning ecosystems, classroom management, and Islamic educational principles. Concept synthesis is carried out through the categorization and integration of key themes from various scientific sources. The results of the study indicate that a conducive classroom environment from an Islamic educational perspective is built through five integrative dimensions: internalization of moral values, adaptive physical classroom design, proportional technology integration, contextual project-based learning, and systemic collaboration between schools, families, and communities. This article offers a conceptual model that places spiritual values ​​at the core of integrating all components of the learning ecosystem.